2012
DOI: 10.1136/bmj.e5205
|View full text |Cite
|
Sign up to set email alerts
|

Managing patients with multimorbidity: systematic review of interventions in primary care and community settings

Abstract: Objective To determine the effectiveness of interventions designed to improve outcomes in patients with multimorbidity in primary care and community settings.Design Systematic review.Data sources Medline, Embase, CINAHL, CAB Health, Cochrane central register of controlled trials, the database of abstracts of reviews of effectiveness, and the Cochrane EPOC (effective practice and organisation of care) register (searches updated in April 2011).Eligibility criteria Randomised controlled trials, controlled clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
468
1
14

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(488 citation statements)
references
References 33 publications
5
468
1
14
Order By: Relevance
“…In contrast, the prevalence of multimorbidity with a mix of physical and mental health conditions is higher among most socioeconomically deprived groups when compared to the least deprived ones [3]. Older adults with multimorbidity who are more likely to experience loss of physical functioning, develop mental health related issues and have difficulties with adherence to multiple medications [7] are the main users of healthcare. It is estimated that medical consultations are almost 4-fold and healthcare costs are 5.5 times higher among older adults with multimorbidity when compared to those without multimorbidity [8].…”
Section: Short Communicationmentioning
confidence: 80%
“…In contrast, the prevalence of multimorbidity with a mix of physical and mental health conditions is higher among most socioeconomically deprived groups when compared to the least deprived ones [3]. Older adults with multimorbidity who are more likely to experience loss of physical functioning, develop mental health related issues and have difficulties with adherence to multiple medications [7] are the main users of healthcare. It is estimated that medical consultations are almost 4-fold and healthcare costs are 5.5 times higher among older adults with multimorbidity when compared to those without multimorbidity [8].…”
Section: Short Communicationmentioning
confidence: 80%
“…The location where the studies were conducted may also have influenced the results, as the main surveys were often performed in large urban centers 21 . The outcome of multimorbidity was not associated with the place of residence in systematic analysis, however 19 .…”
Section: Discussionmentioning
confidence: 99%
“…There was a loss of 6% (21), giving a total of 331 individuals. To make up the sample, 345 of the 992 elderly persons living in the municipality of Estação were randomly added.…”
Section: Methodsmentioning
confidence: 99%
“…[172][173][174] One review of integrated funds for health and social care found mixed evidence of impacts on health outcomes, costs or resource use. 173 Barriers to integrated budgets included difficulties in implementing financial integration and differences in performance frameworks, priorities, governance and information systems.…”
Section: Consensus Conferencementioning
confidence: 99%
“…However, none of these reviews focused specifically on integrated care for people with dementia and comorbid health conditions and there is limited evidence on the care of patients with multimorbidity. 174 Integration on a smaller level was also recommended, for example linking community opticians and optometrists with memory clinics. A recent retrospective audit found evidence to suggest that a combined clinic with neurological, ophthalmic and psychiatric input is a potentially effective way to diagnose and manage complex vision problems in older people, including those with cognitive impairment.…”
Section: Consensus Conferencementioning
confidence: 99%